TRADITIONAL COMPLEMENTARY AND ALTERNATIVE MEDICINE: KNOWLEDGE, ATTITUDES AND PRACTICES OF HEALTH CARE WORKERS IN HIV AND AIDS CLINICS IN DURBAN HOSPITALS - Mbutho, Nozuko P; Gqaleni, Nceba; Korporaal, Charmaine M. (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Traditional complementary and alternative medicine (TCAM) has been reported to be commonly used among individuals with HIV and AIDS disease. However a lack of communication between health care workers (HCWs) and patients as well as between HCWs and TCAM practitioners has been identified as one of the challenges that may adversely affect treatment of HIV and AIDS patients. With improved and sustained communication HCWs, patients and TCAM practitioners would be able to make informed decisions with regards to best treatment practices based on the knowledge of what is safe, effective and what is not. In order to establish a baseline understanding of the current status of interaction and communication between HCWs and TCAM profession in Durban, South Africa, the purpose of the study was to investigate the knowledge, attitudes and practices of HCWs in the HIV and AIDS clinics towards TCAM professions. Data was collected by means of anonymous self-administered questionnaire which was distributed to HCWs in the HIV and AIDS clinics. Out of 161 HCWs in the HIV and AIDS clinics 81 HCWs returned the questionnaires resulting in 50% response rate. The results showed that participants did not possess a basic knowledge of TCAM. Out of 81 participants 23 (28%) scored zero in a true or false knowledge assessment question.